Grain boundary diffusion method of neodymium iron boron rare earth permanent magnet material
By using rare earth fluoride and oxide mixture as diffusion sources, combined with powder metallurgy and multi-stage diffusion treatment, the problem of small increase in coercive force in grain boundary diffusion of Ce-containing neodymium iron boron magnets is solved, and efficient diffusion of rare earth elements is achieved, which significantly improves the coercive force and magnetic properties of the magnets, while reducing costs.
Patent Information
- Application Number
- CN202510061788.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-11
AI Technical Summary
During the grain boundary diffusion process of Ce, the existing NdFeB rare earth permanent magnet materials contain small coercive force increase and limited diffusion depth, resulting in poor magnetic performance.
A mixture of rare earth fluoride and rare earth oxides is used as the diffusion source to prepare neodymium iron boron sintered magnets through powder metallurgy, and primary and secondary diffusion treatments are performed in a vacuum sintering furnace. Combined with low-temperature tempering treatment, the diffusion depth and utilization rate of rare earth elements are improved.
The coercive force of the neodymium iron boron magnet is significantly improved, forming a complete core-shell structure, ensuring that the residual magnetism and maximum magnetic energy content of the magnet are not reduced, and at the same time, the use of heavy rare earths is significantly reduced and the cost is reduced.
Smart Images

Figure CN119811816A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic materials, in particular to a grain boundary diffusion method of a neodymium iron boron rare earth permanent magnetic material. Background Art
[0002] Sintered Nd2Fe 14 B rare earth permanent magnet materials have high magnetic energy product (59.5MGOe) and are widely used in wind power generation, electric vehicles and other fields. In recent years, researchers have explored the use of Ce to partially replace rare earths (RE) such as Pr / Nd to reduce costs, but this causes coercivity (H cj ) and its heat resistance is greatly reduced. In order to further improve the H ci , usually grain boundary diffusion of Dy or Tb is used, and the main diffusion techniques include coating, evaporation, sputtering, electrophoretic deposition and screen printing.
[0003] Nd-Fe-B magnets are made of Nd2Fe 14 The magnet is composed of a B matrix phase, a rare earth (RE)-rich grain boundary phase and a small amount of B-rich phase. The magnetic properties of the magnet mainly come from Nd2Fe 14 Phase B. Nd2Fe 14 Phase B has a tetragonal structure with a space group of P42 / mnm and a high magnetocrystalline anisotropy field (H A ), while high H A It is the prerequisite for the material to obtain high coercivity and thermal stability. Grain boundary diffusion (GBD) Dy or Tb can obtain higher H A (Nd,Dy / Tb)2Fe 14 B hard magnetic shell, inhibits the nucleation reversal of anti-magnetization domain, and improves coercivity. 30 Co 1.0 Cu 0.15 Zr 0.12 Ga 0.3 B 0.94 Fe bal Magnets undergo grain boundary diffusion Dy 70 Al 10 Ga 20 When the main phase is formed, a continuous Dy-rich shell and rare earth-rich grain boundary phase are formed outside the main phase grains, and a high H cj (20kOe), ΔH cj Up to 6.48kOe. For Ce-free (Pr, Nd) 31.2 Co 12 Cu 0.2 Fe bal Al 0.3 Zr 0.1 B1 (wt.%) Magnet diffusion Dy70 Al 10 Cu 20 When high H cj (17.5kOe), ΔH cj As high as 9.6kOe, an obvious core-shell structure can be observed at 500μm.
[0004] However, when Ce replaces RE (RE = Pr, Nd) elements in the alloy, it is easy to form a second phase of REFe2 containing Ce, which hinders the diffusion of rare earth elements such as Dy and Tb, making the H cj The increase (ΔH cj ) is smaller. (Nd,Pr) 22.9 Ce 7.6 Fe bal M 1.0 B 1.0 (M=Co,Al,Cu,Ga,Zr)Magnet grain boundary diffusion (Nd,Pr)H x After, H cj (12.3kOe) only increased by 1.5kOe, and it was found that Ce segregated and gathered on the surface of the magnet and at the triangular grain boundary, and formed REFe2 phase, which hindered the diffusion of Nd / Pr, and the diffusion depth was only 80μm. x Yes 0.3 Nd 0.7 ) 31.5 Fe bal M 2.02 B 0.96 When (M=Al,Cu,Ga,Zr) magnets diffused, a large amount of (Tb,Ce)Fe2 grain boundary phase was formed, which hindered the diffusion of Tb. The researchers further found that ΔH cj As Ce / TRE=16wt% Ce5Pr 6.5 Nd 19.5 M 1.6 B 0.92 Fe bal (M=Cu,Co,Ga,Ti,Al)Magnetic Diffuse Dy 80 Nd 10 Al 10 , H cj From 14.0kOe to 20.9kOe, an increase of 48.8%; for Ce7(PrNd) with Ce / TRE=22wt.% 24.5 Co2Ga 0.1 Al 0.1 Ti 0.2 B 0.92 Fe bal Magnet diffusion Dy80 Al 10 Cu 10 After, H cj From 15.9kOe to 21.0kOe, an increase of 32.6%. For Ce / TRE = 46wt% Ce 14.5 (Nd / Pr) 9.5 G 7.3 B1 1.1 Co 0.2 Cu 0.1 Fe bal Magnet diffusion Dy 70 Cu 30 When the discontinuous grain boundary phase hinders the diffusion of Dy element, resulting in a strong coupling effect between the main phase grains. cj It only increased by 2.5kOe (from 7.2kOe to 9.7kOe). It can be seen that during the grain boundary diffusion process of Nd-Ce-Fe-B magnets with high Ce substitution, impurities such as CeFe2 phase and Ce oxide in the grain boundary reduce the continuity of the grain boundary phase, limit the diffusion depth of heavy rare earth elements, and are not conducive to the improvement of the coercive force of Nd-Ce-Fe-B magnets. Therefore, during the grain boundary diffusion process of Nd-Ce-Fe-B magnets, it is very important to develop efficient heavy rare earth diffusion sources and increase the diffusion depth of heavy rare earth elements. Summary of the invention
[0005] Aiming at the technical problem that the existing Ce-containing NdFeB rare earth permanent magnet material has poor diffusion effect and small coercive force improvement, the present invention provides a grain boundary diffusion method for NdFeB rare earth permanent magnet material, especially a grain boundary diffusion method for Ce-containing NdFeB rare earth permanent magnet material, which can greatly improve the grain boundary diffusion depth of rare earth elements such as Tb, Dy, PrNd, and improve the coercive force of the alloy. The method has little effect on the remanence while improving the coercive force, thereby improving the magnetic properties of the material. On the premise of obtaining equal magnetic properties, the amount of heavy rare earth is significantly reduced, reducing costs.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a grain boundary diffusion method of NdFeB rare earth permanent magnet material, which comprises the following steps:
[0007] (1) Preparation of sintered NdFeB diffusion matrix: using boron, rare earth, iron and iron-substituting elements as raw materials, a quick-setting sheet is prepared by a quick-setting process, and then the quick-setting sheet is crushed into alloy magnetic powder by hydrogen crushing and air flow grinding. The alloy magnetic powder is oriented and formed under an external magnetic field, and then isostatically pressed, and then sintered in a vacuum sintering furnace, and air-cooled to room temperature in the furnace to obtain a NdFeB sintered magnet;
[0008] (2) Preparation of diffusion source: The diffusion source is a suspension slurry consisting of a mixture of rare earth fluoride and rare earth oxide and an appropriate amount of organic solvent;
[0009] (3) processing the NdFeB sintered magnet obtained in step (1) into a required size as a diffusion matrix, degreasing and pickling the magnet, and then subjecting the magnet to grain boundary diffusion treatment. Then, coating the diffusion source prepared in step (2) on the surface of the diffusion matrix, and drying the coated magnet in a vacuum drying oven.
[0010] (4) The magnet dried in step (3) is subjected to a primary diffusion treatment and then to a secondary low-temperature tempering treatment.
[0011] Preferably, the total content of rare earth elements in the alloy magnetic powder is 28-33wt%, of which the Ce content is 0-15wt%, the B content is 0.85-1.0wt%, and the rest is Fe and at least one of the Fe-substituting elements Cu, Al, Ga, Zr, Ti, Cu, Co, Nb, and Mo.
[0012] Preferably, the quick-setting sheet is crushed into alloy magnetic powder with an average particle size of about 1 to 5 μm, the alloy magnetic powder is oriented and formed under an external magnetic field of 1.8 to 2.5 T, and then isostatically pressed under a pressure of 150 to 200 MPa, and then kept in a vacuum sintering furnace at 1000 to 1065° C. for 3 to 10 hours, and the vacuum degree is better than 10×10 -2 Pa.
[0013] Preferably, the rare earth fluoride includes one or more of DyF3, DyF2, DyF, TbF3, TbF2, TbF, PrF3, PrF2, PrF, NdF3, NdF2, NdF, etc., and the rare earth oxide includes one or more of Dy2O3, Tb2O3, Nd2O3, Pr2O3, etc.; the rare earth fluoride accounts for 60-95% of the weight of the mixture, and the rare earth oxide accounts for 5-40% of the weight of the mixture.
[0014] Preferably, the grain size of the rare earth fluoride is 100 nm to 30 μm, and the grain size of the rare earth oxide is 3 nm to 20 μm.
[0015] Furthermore, the grain size of the rare earth fluoride is 200nm-10μm, and the grain size of the rare earth oxide is 3nm-10μm.
[0016] Furthermore, the grain size of the rare earth fluoride is 500nm-5μm, and the grain size of the rare earth oxide is 5nm-500nm.
[0017] Preferably, the organic solvent includes one or more of anhydrous ethanol, acetone, isopropanol, petroleum ether and gasoline.
[0018] Preferably, when the diffusion source is coated on the surface of the diffusion substrate, the thickness of the coating layer is less than or equal to 0.5 mm, and the diffusion amount of the rare earth element is 0.2-1.0 wt% of the weight of the magnet; the temperature of the vacuum drying oven is 50-100° C., and the insulation time is 1-3 h.
[0019] Preferably, the magnet after drying is first subjected to primary diffusion treatment at a temperature of 800 to 950°C, kept at this temperature for 2 to 30 hours, and then air-cooled in the furnace to a temperature below 200°C; then subjected to secondary low-temperature tempering treatment at a temperature of 400 to 600°C for 1 to 6 hours, and air-cooled in the furnace to a temperature below 200°C; during the diffusion treatment, the vacuum degree in the vacuum sintering furnace is better than 1×10 -2 Pa.
[0020] It can be seen from the above technical solutions that the diffusion method provided by the present invention has a simple process and can effectively improve the coercive force of NdFeB magnets, especially the coercive force of Ce-containing magnets, which is reflected in the following aspects: improving the anisotropy field on the grain surface, while improving the grain boundary microstructure, effectively increasing the diffusion depth, so that the coercive force of the magnet is significantly improved, and it can also ensure that the original remanence and maximum magnetic energy product of the magnet are not significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Surface X-ray diffraction patterns of the magnets were obtained for Comparative Example 1 and Example 1.
[0022] Figure 2 It is the DSC thermal analysis curve diagram of the pure DyF3 of comparative example 2, the pure Dy2O3 of comparative example 3 and the DyF3 / Dy2O3 mixed powder diffusion source in embodiment 1.
[0023] Figure 3 The diffusion depth and concentration of Dy in the alloy after diffusion of pure DyF3 in comparative example 2, pure Dy2O3 in comparative example 3 and DyF3 / Dy2O3 in example 1 are shown.
[0024] Figure 4 This is the core-shell structure distribution diagram of the Dy element in Example 1 at a distance of 1200 μm from the surface. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with the accompanying drawings. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0026] The present invention provides a method for grain boundary diffusion of NdFeB rare earth permanent magnet material, which comprises the following steps:
[0027] (1) Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets are prepared by powder metallurgy. First, boron, rare earth, iron and iron-substituting elements are used as raw materials. Quick-setting sheets are prepared by quick-setting process. Then, the quick-setting sheets are crushed into alloy magnetic powder with an average particle size of about 1 to 5 μm by hydrogen crushing and air flow grinding. The magnetic powder is oriented and formed under an external magnetic field of 1.8 to 2.5 T, and then isostatically pressed under a pressure of 150 to 200 MPa. Then, it is kept at 1000 to 1065 ° C in a vacuum sintering furnace for 3 to 10 hours, and the vacuum degree is better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace to obtain a NdFeB sintered magnet, which is a sintered NdFeB diffusion matrix. The sintered sample can be directly diffused or annealed. The total content of rare earth elements in the alloy magnetic powder is 28-33wt%, of which Ce content is 0-15wt%, B content is 0.85-1.0wt%, and the rest is Fe and Fe-substituting elements Cu, Al, Ga, Zr, Ti, Cu, Co, Nb, Mo, etc.
[0028] (2) Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of rare earth fluoride and rare earth oxide and an appropriate amount of organic solvent. Among them, rare earth fluoride includes but is not limited to one or more of DyF3, DyF2, DyF, TbF3, TbF2, TbF, PrF3, PrF2, PrF, NdF3, NdF2, NdF, etc., and rare earth oxide includes but is not limited to one or more of Dy2O3, Tb2O3, Nd2O3, Pr2O3, etc. Rare earth fluoride accounts for 60-95% of the weight ratio of the mixture, and rare earth oxide accounts for 5-40% of the weight ratio of the mixture. The grain size of rare earth fluoride is 100nm-30μm, and the grain size of rare earth oxide is 3nm-20nm. The better grain size of rare earth fluoride is 200nm-10μm, and the better grain size of rare earth oxide is 3nm-10μm. The best crystal size of rare earth fluoride is 500nm-5μm, and the best crystal size of rare earth oxide is 5nm-500nm. The organic solvent includes one or more of anhydrous ethanol, acetone, isopropanol, petroleum ether, gasoline, etc.
[0029] (3) Processing the diffusion matrix obtained in step (1) into the required size, degreasing, pickling and then grain boundary diffusion treatment, coating the diffusion source prepared in step (2) on the surface of the magnet, the thickness of the coating layer is less than or equal to 0.5 mm, and the diffusion amount of the rare earth element is 0.2-1.0 wt% of the weight of the magnet. Then drying the coated magnet in a vacuum drying oven at a temperature of 50-100° C. for a holding time of 1-3 hours.
[0030] (4) Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. First, primary diffusion treatment is carried out at a temperature of 800-950°C. After keeping the temperature for 2-30 hours, the furnace is air-cooled to a temperature below 200°C. Secondary low-temperature tempering treatment is then carried out at a temperature of 400-600°C for 1-6 hours. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is better than 1×10 -2 Pa. The specific implementation is as follows:
[0031] Comparative Example 1:
[0032] Preparation of NdFeB sintered magnets (Pr, Nd) by powder metallurgy 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0033] The annealing process of the alloy is: first, keep it at 900℃ for 20h, then air cool it in the furnace to less than 200℃; then, treat it at 500℃ for 3h, then air cool it in the furnace to less than 200℃. The vacuum degree in the vacuum sintering furnace during the annealing process is 5×10 -3 Pa.
[0034] The magnetic properties of the alloy are: B r =12.46kGs, H cj =11.47kOe, (BH) max =36.8MGOeComparative Example 2:
[0035] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10-2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0036] 2. Preparation of diffusion source. The diffusion source is a suspension slurry consisting of DyF3 and an appropriate amount of anhydrous ethanol, wherein the grain size of DyF3 is 5 μm.
[0037] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment, and the diffusion source prepared in step 2 is coated on the surface of the magnet, the coating layer thickness is 0.4 mm, and the diffusion amount of Dy is 0.8 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 80° C. for 2 h.
[0038] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to a stage diffusion treatment in a vacuum sintering furnace. First, the primary diffusion treatment is carried out at a temperature of 900°C. After keeping the temperature for 20 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 500°C for 3 hours, and the furnace is air-cooled to a temperature below 200°C. During the diffusion treatment, the vacuum degree in the vacuum sintering furnace is 5×10 -3 Pa.
[0039] The magnetic properties of the alloy after diffusion are: B r =12.49kGs, H cj =14.51kOe, (BH) max =36.6MGOeComparative Example 3:
[0040] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0041] 2. Preparation of diffusion source. The diffusion source is a suspension slurry consisting of Dy2O3 and an appropriate amount of anhydrous ethanol. The grain size of Dy2O3 is 5 μm.
[0042] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment, and the diffusion source prepared in step 2 is coated on the surface of the magnet, the coating layer thickness is 0.4 mm, and the diffusion amount of Dy is 0.8 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 80° C. for 2 h.
[0043] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. The primary diffusion treatment is first carried out at a temperature of 900°C. After keeping the temperature for 20 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 500°C for 3 hours. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0044] The magnetic properties of the alloy after diffusion are: B r =12.53kGs, H cj =12.86kOe, (BH) max =36.5MGOeExample 1:
[0045] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0046] 2. Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of (DyF3+Dy2O3) and an appropriate amount of anhydrous ethanol. The ratio of DyF3 to Dy2O3 in the mixture is 80:20 (weight ratio). The grain size of DyF3 is 5μm, and the grain size of Dy2O3 is 100nm.
[0047] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment, and the diffusion source prepared in step 2 is coated on the surface of the magnet, the coating layer thickness is 0.4 mm, and the diffusion amount of Dy is 0.8 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 80° C. for 2 h.
[0048] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. The primary diffusion treatment is first carried out at a temperature of 900°C. After keeping the temperature for 20 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 500°C for 3 hours. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0049] The magnetic properties of the alloy after diffusion are: B r =12.38kGs, H cj =18.09kOe, (BH) max =36.7MGOeExample 2:
[0050] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0051] 2. Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of (DyF3+Dy2O3) and an appropriate amount of acetone. The ratio of DyF3 to Dy2O3 in the mixture is 95:9 (weight ratio). The grain size of DyF3 is 30 μm, and the grain size of Dy2O3 is 20 nm.
[0052] 3. The magnet treated in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment. The diffusion source prepared in step 2 is coated on the surface of the magnet. The coating layer has a thickness of 0.3 mm and the diffusion amount of Dy is 1.0 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 50° C. for 3 h.
[0053] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. First, the primary diffusion treatment is carried out at a temperature of 800°C. After keeping the temperature for 30 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 400°C for 6 hours, and the furnace is air-cooled to a temperature below 200°C. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0054] The magnetic properties of the alloy after diffusion are: B r =12.5kGs, H cj =15.5kOe, (BH) max =36.4MGOeExample 3:
[0055] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0056] 2. Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of (DyF3+Dy2O3) and an appropriate amount of acetone. The ratio of DyF3 to Dy2O3 in the mixture is 60:40 (weight ratio). The grain size of DyF3 is 10 μm, and the grain size of Dy2O3 is 5 μm.
[0057] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment. The diffusion source prepared in step 2 is coated on the surface of the magnet. The coating layer has a thickness of 0.2 mm and the diffusion amount of Dy is 0.2 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 100° C. for 3 h.
[0058] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. First, primary diffusion treatment is carried out at a temperature of 950°C. After keeping the temperature for 2 hours, the furnace is air-cooled to a temperature below 200°C. Then, secondary low-temperature tempering treatment is carried out at a temperature of 600°C for 1 hour. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0059] The magnetic properties of the alloy after diffusion are: B r =12.46kGs, H cj =16.74kOe, (BH) max =37.2MGOe
[0060] Embodiment 4:
[0061] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0062] 2. Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of (TbF3+Pr2O3) and an appropriate amount of anhydrous ethanol. The ratio of TbF3 to Pr2O3 in the mixture is 80:20 (weight ratio). The grain size of TbF3 is 5μm, and the grain size of Pr2O3 is 50nm.
[0063] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment. The diffusion source prepared in step 2 is coated on the surface of the magnet. The thickness of the coating layer is 0.4 mm, and the diffusion amount of Tb\Pr is 0.8 wt % of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 80°C for 2 h.
[0064] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. The primary diffusion treatment is first carried out at a temperature of 900°C. After keeping the temperature for 20 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 500°C for 3 hours. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0065] The magnetic properties of the alloy after diffusion are: B r =12.45kGs, H cj =20.78kOe, (BH) max =36.6MGOe
[0066] Embodiment 5:
[0067] 1. Preparation of sintered NdFeB diffusion matrix. Sintered NdFeB magnets (Pr, Nd) are prepared by powder metallurgy. 20 Ce 11 Fe bal (Cu,Ga,Zr) 1.0 B 0.97 (wt.%). The quick-setting sheet was prepared by the quick-setting process, and then the quick-setting sheet was crushed into alloy magnetic powder with an average particle size of about 3μm by hydrogen crushing and air flow grinding. The magnetic powder was oriented and formed under an external magnetic field of 2.0T, and then isostatically pressed under a pressure of 200MPa. Then, it was kept at 1060℃ in a vacuum sintering furnace for 5h, and the vacuum degree was better than 10×10 -2 Pa, the sintered magnet is air-cooled to room temperature in the furnace.
[0068] 2. Preparation of diffusion source. The diffusion source is a suspension slurry composed of a mixture of (PrF3+Nd2O3) and an appropriate amount of anhydrous ethanol. Among them, PrF3:Nd2O3 in the mixture is 80:20 (weight ratio). The grain size of PrF3 is 5μm, and the grain size of Nd2O3 is 50nm.
[0069] 3. The magnet processed in step 1 is processed into the required size, degreased, pickled, dried, and then subjected to grain boundary diffusion treatment. The diffusion source prepared in step 2 is coated on the surface of the magnet. The thickness of the coating layer is 0.4 mm, and the diffusion amount of Nd\Pr is 0.8 wt% of the weight of the magnet. The coated magnet is then dried in a vacuum drying oven at 80°C for 2 hours.
[0070] 4. Grain boundary diffusion treatment. The magnets in step 3 are subjected to secondary diffusion treatment in a vacuum sintering furnace. The primary diffusion treatment is first carried out at a temperature of 900°C. After keeping the temperature for 20 hours, the furnace is air-cooled to a temperature below 200°C. Then, the secondary low-temperature tempering treatment is carried out at a temperature of 500°C for 3 hours. The vacuum degree in the vacuum sintering furnace during the diffusion treatment is 5×10 -3 Pa.
[0071] The magnetic properties of the alloy after diffusion are: B r =12.42kGs, H cj =15.11kOe, (BH) max =36.5MGOe From the above comparative examples and embodiments, it can be seen that:
[0072] 1. The diffusion source of rare earth fluoride and rare earth oxide co-diffusion can form a low melting point RE-OF phase at low temperature, increase the diffusion driving force of rare earth elements, promote the grain boundary diffusion of rare earth elements, and effectively form Nd2Fe with rich Dy\Tb\Pr\Nd shell 14 Phase B.
[0073] Figure 1 The surface X-ray diffraction patterns of the magnets were obtained for Comparative Example 1 and Example 1. As can be seen from the figure, the surface layer of the original alloy of Comparative Example 1 is mainly composed of tetragonal (Nd, Ce)2Fe 14 B is the main phase; and after diffusion of DyF3 / Dy2O3, the surface layer of the alloy in Example 1 is mainly (Nd, Ce, Dy)2Fe 14 B main phase, but a small amount of cubic structure RE-OF second phase is formed. The formation of RE-OF phase is the result of the reaction between DyF3 and oxide, Dy2O3+2DyF3=Dy4O3F6.
[0074] Figure 2The DSC thermal analysis curve test results of the pure DyF3 in the comparative example 2 and the DyF3 / Dy2O3 mixed powder diffusion source in the embodiment 1 show that DyF3 decomposes during the heating process. There is a small DSC endothermic reaction platform before 600°C, but there is a large endothermic peak between 660 and 950°C, and the maximum value of the endothermic peak appears at 840°C, proving that DyF3 will decompose to form Dy at 660-840°C during the heating process. The endothermic peak of DyF3 / Dy2O3 is a single-peak structure, and the maximum value appears at 340°C. It can be seen that DyF3 and Dy2O3 reacted before about 340°C and generated a new phase, RE-OF phase. The applicant discovered for the first time that the DyF3 / Dy2O3 composite diffusion source can reduce the decomposition temperature of DyF3, facilitating the diffusion of Dy atoms into Nd2Fe 14 Phase B provides the driving force. Dy in Dy4O3F6 phase 3+ Diffusion into Nd2Fe 14 In the main phase B, (Nd,Dy)2Fe is formed 14 Phase B.
[0075] 2. The co-diffusion of rare earth fluorides and rare earth oxides effectively reduces the enrichment of rare earth elements Dy\Tb\Pr\Nd in the surface area, improves the utilization rate of rare earth elements, and saves costs.
[0076] See also Figure 3 In the single Dy2O3 diffusion magnet in comparative example 3, the diffusion depth of Dy is very limited, and only a small amount of Dy element diffuses into the area within about 50μm from the surface. In the single DyF3 diffusion magnet in comparative example 2, Dy and Ce are greatly enriched within about 110μm from the surface, and the enrichment concentration is high. In the single DyF3 / Dy2O3 co-diffused magnet in Example 1, Dy and Ce are slightly enriched within about 50μm from the surface, and the enrichment concentration is lower than that in comparative example 2. On the one hand, the enrichment of Dy element causes a large amount of Dy element to be consumed in the surface layer of the magnet, causing Ce to be significantly enriched in the surface layer. At the same time, only a small amount of Dy can diffuse into the interior of the magnet, reducing the utilization rate of Dy. On the other hand, it causes a large amount of Dy in the surface layer of the magnet to enter the interior of the main phase grains, making the Dy concentration inside the grains higher than the grain boundaries, which has a negative impact on the coercive force.
[0077] 3. The co-diffusion of rare earth fluorides and rare earth oxides effectively increases the diffusion depth and forms a complete core-shell structure, greatly improving the coercive force. Figure 4 In Example 1, the Dy element still has a complete core-shell structure at 1200 μm from the surface, with (Nd, Ce)2Fe 14 Phase B, shell structure is (Nd,Dy)2Fe 14 Phase B significantly increases the coercive force of the diffusion magnet.
Claims
1. A method for grain boundary diffusion of NdFeB rare earth permanent magnet material, characterized by comprising the following steps: (1) Preparation of sintered NdFeB diffusion matrix: using boron, rare earth, iron and iron-substituting elements as raw materials, a quick-setting sheet is prepared by a quick-setting process, and then the quick-setting sheet is crushed into alloy magnetic powder by hydrogen crushing and air flow grinding. The alloy magnetic powder is oriented and formed under an external magnetic field, and then isostatically pressed, and then sintered in a vacuum sintering furnace, and air-cooled to room temperature in the furnace to obtain a NdFeB sintered magnet; (2) Preparation of diffusion source: The diffusion source is a suspension slurry consisting of a mixture of rare earth fluoride and rare earth oxide and an appropriate amount of organic solvent; (3) processing the NdFeB sintered magnet obtained in step (1) into a required size as a diffusion matrix, degreasing and pickling the magnet, and then subjecting the magnet to grain boundary diffusion treatment. Then, coating the diffusion source prepared in step (2) on the surface of the diffusion matrix, and drying the coated magnet in a vacuum drying oven. (4) The magnet dried in step (3) is subjected to a primary diffusion treatment and then to a secondary low-temperature tempering treatment.
2. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 1, characterized in that: The total content of rare earth elements in the alloy magnetic powder is 28-33wt%, of which the Ce content is 0-15wt%, the B content is 0.85-1.0wt%, and the rest is Fe and at least one of Fe-substituting elements Cu, Al, Ga, Zr, Ti, Cu, Co, Nb, and Mo.
3. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 2, characterized in that: The quick-setting sheet is crushed into alloy magnetic powder with an average particle size of about 1 to 5 μm, the alloy magnetic powder is oriented and formed under an external magnetic field of 1.8 to 2.5 T, and then isostatically pressed under a pressure of 150 to 200 MPa, and then kept in a vacuum sintering furnace at 1000 to 1065° C. for 3 to 10 hours, and the vacuum degree is better than 10×10 -2 Pa.
4. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 1, 2 or 3, characterized in that: The rare earth fluoride includes one or more of DyF3, DyF2, DyF, TbF3, TbF2, TbF, PrF3, PrF2, PrF, NdF3, NdF2, and NdF; the rare earth oxide includes one or more of Dy2O3, Tb2O3, Nd2O3, and Pr2O3; the rare earth fluoride accounts for 60 to 95% of the weight of the mixture, and the rare earth oxide accounts for 5 to 40% of the weight of the mixture.
5. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 4, characterized in that: The grain size of the rare earth fluoride is 100nm-30μm, and the grain size of the rare earth oxide is 3nm-20μm.
6. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 5, characterized in that: The grain size of the rare earth fluoride is 200nm-10μm, and the grain size of the rare earth oxide is 3nm-10μm.
7. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 6, characterized in that: The grain size of the rare earth fluoride is 500nm-5μm, and the grain size of the rare earth oxide is 5nm-500nm.
8. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 4, characterized in that: The organic solvent includes one or more of anhydrous ethanol, acetone, isopropanol, petroleum ether and gasoline.
9. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 1, 2 or 3, characterized in that: When the diffusion source is coated on the surface of the diffusion substrate, the thickness of the coating layer is less than or equal to 0.5 mm, and the diffusion amount of the rare earth element is 0.2-1.0 wt% of the weight of the magnet; the temperature of the vacuum drying oven is 50-100° C., and the insulation time is 1-3 hours.
10. The grain boundary diffusion method of NdFeB rare earth permanent magnet material according to claim 9, characterized in that: The magnet after drying is first subjected to primary diffusion treatment at a temperature of 800-950°C, kept at this temperature for 2-30 hours, and then air-cooled in the furnace to a temperature below 200°C; then, secondary low-temperature tempering treatment is carried out at a temperature of 400-600°C for 1-6 hours, and air-cooled in the furnace to a temperature below 200°C; during the diffusion treatment, the vacuum degree in the vacuum sintering furnace is better than 1×10 -2 Pa.
Citation Information
Patent Citations
Method for improving magnetic performance of sintered NdFeB through grain boundary diffusion
CN105489335A
Diffusion-sintering continuous RE-Fe-B magnet and preparation method thereof
CN106128672A
Modified NdFeB magnet and fabrication method thereof
CN106128680A
High-coercivity sintered neodymium iron boron permanent magnet material and manufacturing method thereof
CN109616310A
Method for producing rare earth permanent magnet
KR1020180068272A
Cited By
High-cerium grain boundary diffusion matrix with high thermal attenuation resistance and grain boundary diffusion process thereof
CN120565221A
High-consistency neodymium-iron-boron magnet and preparation method thereof
CN121148837A
High-consistency neodymium-iron-boron magnet and method for manufacturing the same
CN121148837B
La pre-doped high-cerium neodymium-iron-boron magnet and grain boundary diffusion preparation method
CN121839337A